The strike, human rights and its effectiveness in the colombian legal order (2022)
The strike, understood as a constitutional right in which a group of workers, unionized or not, carry out a collective cessation of work in order to pressure the employer to achieve an economic or professional improvement, has all the characteristics to be considered a universally recognized human right. Thus, the objective of this article is to analyze the nature of this right, its usefulness, and the material and substantial obstacles that limit its effective recognition as an expression of the rights of association and collective bargaining in the Colombian legal system.